Shall We Dance? --A Brief History of China Stock Market & QFIIs Scheme - Hua, Fan (2005)
As for a brief introduction, four topics are addressed in this paper: capital market in China, especially equity market; State-Owned-Enterprises (SOEs) in reform, newly implemented QFIIs scheme and last but not least, individual investors. The topics are chosen for two purposes: 1) built up a fundamental conceptual framework, as well as its empirical evolution regarding China stock market for foreign investors who are not familiar with the emerging market yet; 2) indicate major constrains regarding current stage.